1998
DOI: 10.2337/diacare.21.10.1714
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuropathy and High Foot Pressures in Diabetic Foot Ulceration

Abstract: We conclude that both high foot pressures (> or =6 kg/cm2) and neuropathy are independently associated with ulceration in a diverse diabetic population, with the latter having the greater magnitude of effect. In black and Hispanic diabetic patients especially, joint mobility and plantar pressures are less predictive of ulceration than in Caucasians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
245
2
36

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(288 citation statements)
references
References 30 publications
5
245
2
36
Order By: Relevance
“…Several studies have found that increased contact area reduces plantar pressure in the forefoot by 35-44% (3,4,(13)(14)(15)(16)(17). Although in our study the use of an individualized EVA insole inside an Xtra depth shoe increased the effective contact area between foot and insole, this did not result in significant pressure reductions underneath the forefoot.…”
Section: Vas Scorescontrasting
confidence: 46%
See 1 more Smart Citation
“…Several studies have found that increased contact area reduces plantar pressure in the forefoot by 35-44% (3,4,(13)(14)(15)(16)(17). Although in our study the use of an individualized EVA insole inside an Xtra depth shoe increased the effective contact area between foot and insole, this did not result in significant pressure reductions underneath the forefoot.…”
Section: Vas Scorescontrasting
confidence: 46%
“…Inclusion criteria included the following: 1) presence of peripheral sensory neuropathy (objectified using Semmes-Weinstein monofilaments as described by Frykberg et al [4]), 2) absence of important foot deformity (i.e., able to wear manufactured shoes), 3) having no present foot ulceration, 4) having sufficient walking capacity, and 5) having no other diseases of the lower extremity. All patients were informed about the goal of the study in detail and gave their written consent to participate.…”
Section: Subjectsmentioning
confidence: 99%
“…In summary, all the four groups in this study are already at risk of plantar injury due to the presence of DMPN [33]. Further complications, such as plantar ulceration, PFAs and TTAs, increase the risk of plantar injury in this patient population during walking.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, some peoples have hypothesized that flat feet in children, in many cases, can lead to disability in adulthood 11,12) . Increased plantar foot pressures caused by deformity are closely associated with tissue injury and ulceration 13) , and as a source of pain 14,15) .…”
Section: Introductionmentioning
confidence: 99%